Pandangan The Confucian Perspective on Natural Disasters: Yin-Yang Interpretation and the Balance of Nature - Fani Nurmalina; Syafrida Aslami (Al Hikmah, 2026)
This article comprehensively examines the Confucian perspective on natural disasters by interpreting the fundamental concepts of yin-yang dynamics and cosmic balance. Amidst escalating global ecological crises, understanding philosophical and religious frameworks offers profound insights into disaster management. This study employs a qualitative methodology based on a rigorous literature review, utilizing both conceptual and hermeneutic approaches to analyze classical Confucian texts alongside contemporary literature on environmental ethics and disaster studies. The research findings indicate that within the Confucian paradigm, natural disasters are fundamentally not understood as arbitrary divine punishments. Instead, they are interpreted as visible manifestations of moral and ecological imbalances resulting from a profound disharmony between human behavior and the natural order. Confucian ethics heavily emphasizes human moral responsibility, specifically through the implementation of core principles such as ren (humaneness), li (ritual propriety), and the philosophical unity between heaven, humanity, and nature (Tian Ren He Yi), which serve as the essential foundation for restoring cosmic equilibrium. Ultimately, this study significantly contributes to the interdisciplinary discourse on religion and disaster studies by offering a robust Confucian ethical framework. This framework is highly relevant for complementing contemporary scientific approaches and technical strategies in disaster mitigation and ongoing environmental crises